2018
DOI: 10.1038/s41598-017-18654-7
|View full text |Cite
|
Sign up to set email alerts
|

Stratification-induced reorientation of disk settling through ambient density transition

Abstract: Settling due to gravity force is a basic transport mechanism of solid particles in fluids in the Earth. A large portion of particles occurring in nature and used in technical applications are non-spherical. Settling of particles is usually studied in homogeneous ambient conditions, however, stratification is inherent of natural fluids. It has been acknowledged that stratification modifies the velocity of settling spheres and amorphous aggregates. However, the effect of particle shape on the dynamics of settlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 48 publications
(89 reference statements)
5
28
1
Order By: Relevance
“…Experiments were carried out in a tank with interior dimensions 0.060 m × 0.060 m and a height of 0.500 m. The experimental set-up was similar to one used in previous settling experiments performed in the laboratory 60 and is presented in Supplementary Fig. S11.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments were carried out in a tank with interior dimensions 0.060 m × 0.060 m and a height of 0.500 m. The experimental set-up was similar to one used in previous settling experiments performed in the laboratory 60 and is presented in Supplementary Fig. S11.…”
Section: Methodsmentioning
confidence: 99%
“…Instantaneous particle settling velocity, u y , was evaluated from the sequence of recorded images using Particle Tracking Velocimetry method. First, the position and orientation of the particle in each image was assessed by image analysis methods described in previous study 60 . Then, knowing a time step between consecutive frames, the particle time-resolved position was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…The settling of anisotropic bodies, especially ellipsoids and disks, has been considered at moderate Reynolds number (Re 100), under conditions where their motion in a homogeneous fluid reduces to a steady broadside-on fall. Although the background stratification is stabilizing for bodies released broadside-on, density disturbances acting on a slightly tilted oblate or prolate body settling in a stratified fluid may destabilize its initial orientation and make it eventually settle edge-on , Mrokowska 2018. The instability is rooted in the offset between the body axis and the location at which the upward jet emerges at the back of the body (Figure 5a).…”
Section: Anisotropic Deformable and Porous Bodiesmentioning
confidence: 99%
“…Response of the terminal fall velocity to key factors (a) Effects of particle shape Natural particles are hardly spherical. A large variety of non-spherical natural and artificial particles is used in engineering applications; for instance, disc [54], oblate spheroid [55], ice crystals [56], snowflakes [57,58], mineral dust [59], volcanic ash [60] and shell fragments as littoral sediments [15,17]. As a result, the particle shape is worth considering while estimating the drag coefficient and, in turn, the terminal fall velocity [17,61,62].…”
Section: (B) Equilibrium Statementioning
confidence: 99%
“…In addition, the surface irregularity might induce instability to the particle, yielding rotation and vibration of the particle, which eventually reduces the terminal fall velocity. It is worth highlighting that Mrokowska [54] studied specifically the effects of particle shape on a particle settling through a stratified fluid. In a two-layer fluid with a density transition, it was found that a disc exhibits five phases of settling.…”
Section: (B) Equilibrium Statementioning
confidence: 99%